2017
DOI: 10.1177/0020731417722089
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Impact of Healthcare Reforms on Access to Emergency Department and Elective Surgery Services

Abstract: This systematic review sought to identify whether health care reforms led to improvement in the emergency department (ED) length of stay (LOS) and elective surgery (ES) access in Australia, Canada, New Zealand, and the United Kingdom. The review was registered in the PROSPERO database (CRD42015016343), and nine databases were searched for peer-reviewed, English-language reports published between 1994 and 2014. We also searched relevant "grey" literature and websites. Included studies were checked for cited and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 46 publications
0
17
0
1
Order By: Relevance
“…Global efforts to reduce waiting time through health policy have traditionally focused on time to elective procedures after referral and ED waiting time. 7,29,72,85 However, this method of measurement fails to recognize and/or hides other types of waiting times, including time waiting for primary care, specialist medical care, allied health appointments, and time spent physically waiting in waiting rooms. We need greater transparency regarding the range of types of waiting for health services, and systematic enquiry into the reasons or potential targets for interventions.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Global efforts to reduce waiting time through health policy have traditionally focused on time to elective procedures after referral and ED waiting time. 7,29,72,85 However, this method of measurement fails to recognize and/or hides other types of waiting times, including time waiting for primary care, specialist medical care, allied health appointments, and time spent physically waiting in waiting rooms. We need greater transparency regarding the range of types of waiting for health services, and systematic enquiry into the reasons or potential targets for interventions.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…Ray et al 63 performed a subanalysis of 3787 respondents to the American Time Use Survey. Among respondents who reported their clinic time during the 24-hour assessment period, a median (95% CI) of 86 [83][84][85][86][87][88] minutes was spent in-clinic. 63 Those in the lowest income quartile reported a mean [95% CI] clinic time of 91 [87][88][89][90][91][92][93][94][95] minutes compared with those in the highest income quartile, who reported a mean clinic time of 72 [65][66][67][68][69][70][71][72][73][74][75][76][77][78] minutes.…”
Section: Socioeconomic Inequality and Waiting Timementioning
confidence: 99%
“…41 Similarly, the NEAT may result in increasing pressure on ED physicians to achieve the 4-hour rule target. 42 A study conducted in a tertiary hospital in Australia found an increase up to 61% in the total number of imaging requests following the introduction of the 2011 reform compared with the prereform period. 43 Interestingly, this study indicated that the trend was towards more requests in CT and less radiography while other imaging techniques remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Targets to reduce elective surgery waiting lists are prevalent in Organization for Economic Co-operation and Development (OECD) countries,1 2 and various interventions have been explored to reduce waiting times 3. In Australia, although the National Elective Surgery Target (NEST) is an important component of hospital performance measurement,4 median waiting times for elective surgery have increased by around 2% per year over the 5 years 5.…”
Section: Introductionmentioning
confidence: 99%